Relationally Queer A Pink Therapy Guide for Practitioners - Neves, Silva; Davies, Dominic (Taylor & Francis, 2023)
Relationally Queer explores diverse intimate relationship styles and the connections with self for clinicians interested in gender, sex and relationship diversity. Offering readers a more inclusive and queer-friendly way of thinking about relationships, the book covers a range of topics that include intersectionality, consensual non-monogamy, working with shame, intimate partner violence, religious identities, and living with HIV. Exploring beyond a Eurocentric perspective, the book features a chapter on African-centred therapy and also includes the relationships of often erased populations such as bisexual people, sex workers, people with chronic health issues and trans people. The book will help psychosexual and relationship therapists, counsellors and psychologists who work with clients of diverse genders, sexualities and relationships.